2011
DOI: 10.1007/s10517-011-1483-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of peptide Pro-Gly-Pro-Leu under conditions of normal hemostasis and thrombus formation in rats

Abstract: Tetrapeptide Pro-Gly-Pro-Leu in vitro effectively inhibited platelet aggregation over the entire range of studied concentrations (10(-12)-10(-3) M). In concentrations of 10(-9)-10(-3) M it exhibits fibrinolytic activity and in concentrations of 10(-5)-10(-3) M has anticoagulant properties. Under in vivo conditions the analyzed tetrapeptide in a dose of 1 mg/kg increased anticoagulant, total and fibrin depolymerizating activities and increased activity of plasminogen activator. Intravenous administration produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…ACTH(6‐9)PGP enhanced cell viability in the H 2 O 2 , tBH, and KCN cytotoxicity models (Akimov et al, 2021), significantly increased the number of survived cultured cortical neurons in the model of glutamate excitotoxicity (Bakaeva et al, 2020), showed an anxiolytic effect in chronic immobilization stress model (Vorvul et al, 2022). Tetrapeptide PGPL affected blood hemodynamics (Myasoedov et al, 2016; Obergan et al, 2011), reduced the activity of apoptosis (caused by “social” stress) and decreased the levels of caspase‐3 and caspase‐8 in the blood serum of white rats (Yasenyavskaya et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…ACTH(6‐9)PGP enhanced cell viability in the H 2 O 2 , tBH, and KCN cytotoxicity models (Akimov et al, 2021), significantly increased the number of survived cultured cortical neurons in the model of glutamate excitotoxicity (Bakaeva et al, 2020), showed an anxiolytic effect in chronic immobilization stress model (Vorvul et al, 2022). Tetrapeptide PGPL affected blood hemodynamics (Myasoedov et al, 2016; Obergan et al, 2011), reduced the activity of apoptosis (caused by “social” stress) and decreased the levels of caspase‐3 and caspase‐8 in the blood serum of white rats (Yasenyavskaya et al, 2021).…”
Section: Introductionmentioning
confidence: 99%